PENGARUH KUALITAS PRODUK DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN IMPLIKASINYA PADA KEPUASAN KONSUMEN SMARTPHONE XIAOMI DI PUSAT HANDPHONE PGC CILILITAN - Wahyu Murti; Fikri Hendhiyanto Yulian (Jurnal Manajemen FE-UB, 2019)
The study aims to determine the effect of the Effect of Product Quality and Product Prices on PurchaseDecisions Implications on Consumer Satisfaction Smartphone Xiaomi Center PGC Cililitan East JakartaThe data used in this study are primary data obtained from the results of the distribution of questionnaires tovisitors at the Mobile Center PGC Cililitan East Jakarta. The data processing method uses the path analysis methodwith the help of SPSS 24 program.The results showed that method I: Directly the product quality and product price variables had a positive andsignificant effect on purchasing decisions. Method II: Directly variable product quality, product prices, andpurchasing decisions have a positive and significant effect on customer satisfaction. Indirectly, product quality andproduct prices affect consumer satisfaction through purchasing decisions using the Sobel Test method.Keywords: Product quality, Product Prices, Purchasing Decisions, Consumer Satisfaction